Death education among psychology university students: A psychosocial qualitative perspective - Ines Testoni; Martina Gentile; Ciro De Vincenzo (Global Transitions)
Death education, a burgeoning field within psychosocial and educational sciences, addresses how individuals perceive and cope with themes of finitude, terminality, fragility and mortality. It employs a variety of methods including psychodrama, artistic activities, experiential sessions, and theoretical instruction to reduce death anxiety, enhance emotional resilience, and foster a deeper understanding of end-of-life issues. This research adopts a qualitative methodological research design to understand the experience of psychologists in training participating in a death education intervention. For these purposes, we realized n = 3 focus groups involving n = 21 participants from a group of students participating in an end-of-life course in a master's programme in psychology at the University of Padova. Transcriptions of the audio-recorded focus groups were analysed through reflexive thematic analysis, highlighting the dynamic interplay of personal and professional growth processes. Three major themes emerged: “Awareness and Realization of humane finitude”, reflecting students' heightened consciousness of mortality and its implications for life and practice; “Social Validation of Personal Experiences”, underscoring the role of collective discussion in normalizing and enriching individual perspectives; and “Imagining Professional Futures in Palliative Psychology”, which illustrates the participants' emerging sense of identity as future professionals. These findings emphasize the value of integrating death education into psychology curricula, not only to equip students with the competencies required to address end-of-life issues but also to provide safe, reflective spaces for engaging with liminal topics. Such initiatives contribute to shaping more empathetic, self-aware, and resilient psychologists capable of addressing the multifaceted psychosocial and spiritual dimensions of human experience.